2015
DOI: 10.1007/s00417-015-3200-2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immunosuppression with mycophenolate mofetil to prevent corneal graft rejection after high-risk penetrating keratoplasty: a 2-year follow-up study

Abstract: PurposeIn this study, we aimed to evaluate the efficacy and safety of systemic immunosuppression with mycophenolate mofetil (MMF) to prevent corneal graft rejection after high-risk penetrating keratoplasty.MethodsOne hundred and ninety-six consecutive patients who underwent high-risk penetrating keratoplasty defined as the presence of deep vascularization in more than two quadrants, keratouveitis, emergency keratoplasties, and retransplantations were enrolled in the study. Ninety-eight prospectively followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
12
2
Order By: Relevance
“…The rejection rates at 12, 24, and 36 months were 10%, 25%, and 61% in the current study. This was higher than the results of high-risk penetrating keratoplasty in 5 years reported by Chow SP 32 but was lower than that in 2 years reported by Sza ik JP 33 . A failure rate due to graft rejection (25%) was lower than them in the current study.…”
Section: Discussioncontrasting
confidence: 65%
“…The rejection rates at 12, 24, and 36 months were 10%, 25%, and 61% in the current study. This was higher than the results of high-risk penetrating keratoplasty in 5 years reported by Chow SP 32 but was lower than that in 2 years reported by Sza ik JP 33 . A failure rate due to graft rejection (25%) was lower than them in the current study.…”
Section: Discussioncontrasting
confidence: 65%
“…The Australian Graft Registry reported a rejection rate of 16% in PKP performed for any indication in 2015, although they did not break down the data for high risk PKP . Nonetheless, our rate is lower than that reported for PKP in high risk cases . Our failure rate following rejection is comparable to Basu et al, who reported a 57.7% failure rate after 1 or more episodes of endothelial rejection, although they combined the rejection and failure data for a single‐stage and two‐stage procedures .…”
Section: Discussioncontrasting
confidence: 42%
“…Firstly, unlike other immunosuppressive drugs such as corticosteroids, it does not alter the expression of MSC immunomodulatory factors ( 42 ) and has been shown to exert a synergistic effect with MSC in a pre-clinical heart transplant model ( 21 ). Secondly, MMF is currently prescribed to patients receiving high-risk cornea transplants including re-grafts ( 43 , 44 ). Our observation that co-administration of MMF did not diminish the anti-rejection of third-party allo-MSC therapy (and trended toward further increase in rejection-free survival) in this high-risk model provides additional evidence of clinical translational potential.…”
Section: Discussionmentioning
confidence: 99%